LEVEL OF NUTTRITION ADEQUACY, PHYSICAL ACTIVITY AND NUTRITIONAL STATUS OF YOUNG MEN ATHLETES SOCCER SENIOR HIGH SCHOOL IN DENPASAR 2011 - Karyamitha, Ni Luh Gede; Tresna Adhi, Kadek (Medicina, 2013)
Soccer is a favorite sport for  people around the world including in Indonesia. Not only the method of training or talent that will determine the achievement, but the intake of daily nutrients directly proper also provide a positive influence on performance and achievements of athletes. The purpose of this study was to determine the adequacy of nutrition, physical activity, and nutritional status of young men athletes soccer. This study useds cross-sectional method. The number of samples taken as much as 96 athletes from all senior high schools in Denpasar and selected systematic random sampling. Results showed the average level of nutritional adequacy of athletes still in the category of less (<80%). Respectively for energy, carbohydrates, proteins, and fats are 75.95%, 77.24%, 78.96% and 75.83%. If seen the proportion of athletes that sufficient levels of nutrients in enough categories, then each for energy, carbohydrates, proteins, and fats are 58.3%, 57.3%, 51%, and 53.1%. Level of physical activity in athletes only low (56.3%) and moderate category (43.8%). Most athletes have normal nutritional status (94.8%), there was only 1% having thin status, and 4.2% had nutritional status of overweight. The advice can be given to provide knowledges that related with intake of nutrients for the coaches and athletes, increasing physical activity for athletes who have low physical activity, and can be the nutritional status as a selection soccer athletes. However, further research can be done is to measure the physical endurance athletes associated with the intake of nutrients or physical activity.
Keywords: soccer athletes, the level of adequacy of nutrition, physical activity, and nutritional status